Incidence of vocal cord paresis following ultrasound-guided interscalene nerve block: An observational cohort study. Issue 4 (December 2019) - Gritsenko, Karina; Polshin, Victor; Agrawal, Priya; Nair, Singh; Shaparin, Naum; Gruson, Konrad; Tan-Geller, Melin
Abstract : Background: Interscalene brachial plexus block (IBPB) has become a standard practice for perioperative analgesia for shoulder procedures. However, several side effects may occur owing to its anatomic location. We have chosen to evaluate vocal cord paresis and dysphonia following interscalene blocks. Methods: After IRB approval, eight patients undergoing arthroscopic shoulder procedures were recruited into this prospective cohort study. Following informed consent, vocal cords were assessed by standardized fiberoptic evaluation. Subsequently, IBPB was performed under ultrasound (US) guidance. Patients were re-evaluated for vocal cord changes by a repeat fiberoptic assessment one hour following IBPB. Our primary outcome measure was incidence of vocal cord immobility. Results: No patients had diminished vocal cord motion, dysphonia, or dysphagia. Conclusions: Although larger studies are required to determine the true incidence of vocal cord paresis following US-guided IBPB, our results suggest that incidence of unwanted nerve blockade other than brachial plexus is much lower than that previously described. Highlights: IBPB was not associated with vocal cord paresis. Bupivacaine 0.5% (20 mL) produced a therapeutic block in all patients. Future studies with varying anesthetic volumes are needed to validate our findings.